Online Harassment and Systemic Inequality: Experiences of Female Journalists and Activists in Pakistan - Humaira Munir (`, 2025)
How do female journalists and activists in Pakistan perceive the nature, causal factors and sources behind the online harassment? Any action that targets others with force or threats is considered harassment. The use of technology has brought a new era of communication and connectivity, but it has also brought new forms of harassment and violence. Journalists and activists use digital spaces to express their opinions and get harassed in the digital spaces in all over the world. Scholars have delved into the incidents of online harassment to female journalists and activists in Pakistan but those studies don’t shed light on the traumas faced by those victims caused by online harassment. The present study focuses on the traumas faced by female journalists and activists in Pakistan due to the harassment they face in digital environments during the course of their professional life. The study focuses on the feminism theory using intersectional approach to analyze the traumatic experiences. The study relies on the Primary and Secondary data. 10 Semi-structured open ended interviews were conducted to female journalists and activists of Pakistan who have faced online harassment on different social media primarily on Twitter. The findings emphasizes that online harassment is a "symptom and a tool of systemic inequality." This reveals how existing hierarchies of "gender, class, and political power" are replicated and strengthened on digital platforms, which were formerly neutral spaces for free, speech. An intersectional feminist approach calls for a holistic response , one that questions systemic power dynamics, creates digital spaces that are safer and more welcoming, and upholds women's freedom to fully engage in public and political life without worrying about consequences. Significant progress in removing the digital barriers that silence women and uphold inequality can only be achieved by addressing these interlocking aspects of oppression. Keywords: Online harassment, Journalists, Activists, Pakistan, Feminism, Power, Class, Gender